초동발췌를 위한 탄성파 신호분석연구 - 이두성 (물리탐사, 10(2), 2007)
초동발췌 방법과 이와 관련된 오차문제를 고찰하고 자료처리 전산화 측면에서 초동발췌 및 오차계산의 실용적 알고리즘을 제안하였다. 제안한 초동발췌 방법은 2단계로 구성된다. 1) 초동신호 중 트레이스 간 연속성이 양호한 최초의 피크(peak) 또는 트라프(trough)를 발췌한다. 2) 발췌시점 전방 일정구간의 기록을 직선으로 근사화 하고 이 직선의 시간 절편을 초동주시로 한다. 근사화 구간의 길이는 대략 초동 웨이브렛 폭의 1/4보다 다소 작게 설정한다. 초동발췌에 내재된 오차의 정량적인 척도는 기록의 특정시점에 초동의 도착 여부를 판단하는 데 필요한 기록의 길이로 정의한다. 기록의 길이를 나타내는 공식은 신호의 주파수대역과 신호대잡음비의 함수로 표시된다. 3개의 공대공 탄성파기록의 초동을 수동 및 제안한 방법으로 발췌하였고 각 트레이스의 오차한계를 계산하였다. 실험결과 제안한 근사직선 시간절편법의 우수한 성능과 발췌된 초동평가에 있어서 발췌오차의 유용성을 확인하였다. With consideration of the first arrival picking methodology and inherent errors in picking process, I propose,from the computerization point of view, a practical algorithm for picking and error computation. The proposed pickingprocedure consists of 2-step; 1) picking the first coherent peak or trough events, 2) derive a line which approximatesthe record in the interval prior to the pick, and set the intercept time of the line as the first break. The length of fittinginterval used in experiment, is few samples less than 1/4 width of the arriving wavelet. A quantitative measure of theerror involved in first arrival picking is defined as the time length that needed to determine if an event is the first arrivalor not. The time length is expressed as a function of frequency bandwidth of the signal and the S/N ratio. For 3 setsof cross-well seismic data, first breaks are picked twice, by manually, and by the proposed method. And at the samemethod, and the usefulness of the quantitative error measure in pick-quality evaluation. KCI Citation Count: 2